Elementos visuais na propaganda política: um estudo da resposta emocional de eleitores em diferentes cenários nos vídeos de campanha eleitoral - Carlos Magno Machado Dias (2020)
This thesis aims to evaluate qualitative and quantitative qualifications related to the emotional response of monitors to scenery changes in advertising policy videos and, in time, to assess whether there is a relationship between emotional responses to advertising policy videos in each scenario, and voter political orientation and belief system. The experiment was conducted in the laboratory and the monitors who underwent the experiment were between 17 and 60 years old, were invited by accessibility and were students of the business and accounting courses at Senac Minas College. Political Propaganda Video was recorded in the studio using chroma key. We chose to use an actor as a candidate. The text of the electoral propaganda was written in a generic way, randomly inserting words that make up a political agenda of different tendencies. Digital inserts four distinct scenarios for video: a completely white background, a library-like scenario, a popular-home scenario, and a luxury-home scenario. The opinions and images of the face of the devices were collected through a web platform developed exclusively for this purpose. How recorded images of voters were analyzed by the FaceReader® software. Then, as measures of the intensities of validity, excitement, and the seven basic emotions, the statistically compared media. Data processing has made use of both multifactorial and emotion analysis. The data were analyzed in three dimensions: I) we verified statistical differences between the intensities of emotions within the same scenario; II) statistical differences between different emotions and opinions and, III) statistical differences between emotions compared in different scenarios. It found statistical differences between the intensities of emotions in all dimensions in which the data were analyzed. The work allowed the empirical demonstration that, as political propaganda professionals believe, scenarios can potentiate the emotional effects of this type of propaganda.